CORRELATIONSHIP BETWEEN THE LEVEL OF THYROTROPIN RECEPTOR ANTIBODY WITH ACTIVITY AND SEVERITY OF GRAVES’ OPHTHALMOPATHY AT WAHIDIN SUDIROHUSODO HOSPITAL MAKASSAR: Oral Presentation - Observational Study - Ophthalmologist - ARDY GISNAWAN (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Graves’ Ophthalmopathy (GO) is an autoimmune orbital disease with mostly occurs along with hyperthyroidism. The underlying cause of GO is theoretically connected with thyrotropin receptor that activated antigen-presenting cells from thyrotropin-receptor peptides, then attached with T- helper and B cell that produce the level of thyrotropin receptor antibody (TRAb) and cause an enlargement of orbital tissue and increase the level of triiodothyronine (T3) and thyroxine (T4). To determine the active manifestation status from those clinical findings, the Clinical Activity Score (CAS) is utilised. Meanwhile, European Group on Graves' Orbitopathy (EUGOGO) is used to classify the severity of the disease. This research aims to assess the correlation of TRAb levels toward its activity and severity in patients with Graves’ Ophthalmopathy. Methods : Thirty-four patients with Graves’ Ophthalmopathy underwent clinical and laboratory examinations. The result of clinical finding was plotted into CAS to determine its activity status and EUGOGO to classify its severity. TRAb concentration was measured with ELISA or TBII Assays. Results : All patients have high level TRAb. We analysed the level of TRAb with activity and severity. We found a significant result of cofounding variables related to gender and smoking history, with P value 0.011 and 0.017 respectively. There is no statistically significant result TRAb with activity (CAS) P=0.465, and TRAb with Severity (EUGOGO) P=0.812. Conclusion : The level of TRAb is primarily used as diagnostic marker for Graves’ Ophthalmopathy, but they haveno correlation from the level of TRAb with activity and severity patient with Graves’ Ophthalmopathy.